Influence of Store Atmosphere and Sales Promotion on Impulse Buying through Positive Emotion as an Intervening Variable (Study on Charles & Keith Tunjungan) - Wulandari, Elfitra Widia; Andarini, Sonja (Universitas KH. Abdul Chalim Mojokerto, 2025)
The retail industry in Indonesia has achieved success by maintaining the best quality for consumers. Using positive emotion as an intervening variable, this study attempts to ascertain and examine how sales promotions and store atmosphere affect impulsive purchases made by customers of the Charles & Keith Tunjungan Plaza store. Given that the data collected for this kind of research is numerical, a quantitative method is used. Customers who have bought Charles and Keith products and who meet the requirements of being at least eighteen years old and residing in Surabaya comprise the demographic that is the subject of this study. 99 respondents participated in the purposive sampling technique used for the sampling process. Numerous methods, including surveys, books, websites, and other literature, are used to gather data. Google Forms were used to distribute questionnaires as part of the data collection strategy. The Partial Least Square approach, which is enabled by SmartPLS 4.0 software, is used in this study's data analysis to examine the relationship between one or more independent variables and the dependent variable. The study's findings show that sales promotions have no effect on impulse buying, store atmosphere has no effect on impulse buying, sales promotion has an impact on impulse buying, sales promotion and store atmosphere have an impact on positive emotion, positive emotion influences impulse buying, and store atmosphere influences impulse buying through positive emotion.